Kompetensi Dan Employability Dalam Peningkatan Kinerja Karyawan - Ayyu Purnama; Nurana Dwina Bintang; Tia Pratiwi; Muhammad Al-Fatih; Chandra Winata; Aswaruddin Aswaruddin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This article discusses Competency and Employment by applying descriptive analysis methods to explore all sources related to this topic. The data collection approach in this research is through library research, where data sources such as books, scientific journals, literature and other publications become the basis for investigating Competency and Employment. The aim of this research is to understand the importance of competency and work ability in the context of the world of work. Competencies Refer to the combination of knowledge, skills, and attitudes required to succeed in a job or profession. The availability of appropriate competencies really supports improving employee performance, which in turn is closely related to the organization's strategic goals through the processes that occur.